From ritual to metaphor: The semantic shift in the concept of ‘victim' and medieval Christian piety - Galona, Yevgen (2018)
A study of the genealogy of the concept of victim (victima), originally an object of sacrifice [ritualistic meaning], reveals how it became a metaphorical label for a harmed party [figural meaning]. This article rejects the idea presented in earlier scholarship, that the figural meaning of victim (‘a harmed party') emerged through the interpretation of Christ's death in terms of sacrifice within Christian theology. It also seeks to demonstrate that it was not the initial representation of the Passion as a sacrifice that encouraged convergence between the meanings of victim, but rather changes in the presentation of the Crucifixion in late medieval piety. From the High Middle Ages, the marginal figural meaning gradually overcame the original religious one and by the 18th century it had become a primary sense that disconnected the victim from a ritualistic context.